Control of surface temperature of an aluminum alloy billet by air flow during a heating process at elevated temperature - Choi, Young; Park, Joon Hong (Journal of mechanical science and technology, 2016)
The procedure of semi-solid forming is composed of heating a billet, forming, compression holding and ejecting step. There are several methods to heat a billet during semi-solid forming process such as electric heating and induction heating. Usually in semi-solid forming process, induction heating has been adopted to achieve more uniform temperature of semi-solid material. Although induction heating is better method than any others, however, there is still difference of temperature between internal part and surface part of semi-solid material. Worse yet, in case of high liquid fraction of semi-solid material, liquid of the billet will flow down though solid of the billet still remains, which is very difficult to handle. In the present study, induction heating of the billet during thixoforging process with forced surface cooling has been performed to obtain more uniform distribution of temperature, microstructure and shape of the billet. Distribution of temperature of the billets was measured and compared with that of conventional distribution of temperature. Microscopic and macroscopic aspects of the billets were discussed according to location of the measuring points. By this new induction heating method, not only temperature distributions over the whole billet become uniform, but also control of temperature distribution between inside and outside part of the billet is possible as user’s experimental intentions.